Stable Isotope Analysis:A Tool for Certifying Captive or Wild caiman Leather Origin - Simoncini, Melina S.; Marques, Thiago S.; Bassetti, Luis A. B.; Lara, Neliton R. F.; Pierini, Sofía E.; Camargo, Plinio B.; Verdade, Luciano M.; Piña, Carlos I. (Aquatic conservation, 2025)
ABSTRACT Tools to discriminate products from captive and wild sources will improve wildlife sustainability, and stable isotopes of carbon and nitrogen can be potentially useful for this. In this study, we evaluated δ15N and δ13C in Caiman latirostris skins from captive individuals (from Argentina and Brazil), wild individuals (from Argentina), and leathers (from tanned skins) from both captive and wild individuals (from Argentina). In addition, we compared the isotopic signatures of caiman claws from both wild and captive caimans from Brazil. The main goal of this study was to evaluate the possible differences in the variability of δ15N and δ13C between skins, leathers, and claws from wild and captive animals. We found that skins, leathers and claws from the wild individuals had a larger δ15N and δ13C variability compared to samples from captive animals. In addition, tanning did not affect δ15N and δ13C variability. We can thus distinguish skins and leathers from wild and captive animals, which will be useful in governing conservation measures especially in regions where hunting is banned and/or where only farmed individuals can be traded.